Insuficiencia de las sanciones establecidas en el Código del Trabajo respecto a los empleadores que contratan a menores para actividades laborales - Manzano Barragan, Deysi Ximena (2015)
The Labour Code in Article 134 stipulates textually "To forbid any kind of work, whether employees to children and adolescents under the age of fifteen. An employer who violates this prohibition will pay the lesser of fifteen double compensation, will not be it exempt meet all derivative work and social obligations of the employment relationship including all the features and benefits of social security, shall be punished with maximum fine provided for in article 95 of the code of Childhood and Adolescence and the closure of the establishment for repeat this same code in Art. 628 ._ in case of violation of the Labor Code, violations of rules this code will be punished as prescribed in the relevant articles, and when Figado sanction has been the Regional director of Labour may impose fines notwithstanding the provisions of Section 95 of the code of childhood and adolescence. Considering that the penalties provided to employers in the Labour Code are laughable, insufficient merit a review of the Ecuadorian legislation to the Labour Code in its Article 134.628, the same as not closely related to the Constitution of the Republic of Ecuador in the art 35,44,45,46 International Instruments paragraph 2, Code of Childhood and Adolescence, so make an alternative proposal to somehow correct the irisoriedad of fines. With this background and with the help of Ecuadorian law after reviewing the constitution in accordance with Labor Code, Code of Childhood and Adolescence international conventions and treaties Rights of the Child, Comparative law we realize that warrants an immediate reform title of this topic proposed in this thesis. No legislation explain, document on the insufficient sanctions on employers who hire minors for work activities, I make a very close relations hip to child labor, to obtain this result. Being foolish employers who violate the labor law, studying criminal doctrine regarding the criminal liability of typical actions that become anti-juridical prohibition, these vulnerable people are subjected to perform tasks to the detriment of their integrity. Finally punish ejempalrizadora so action is appropriate from my point of view, considering that legal rights and constitutional principles very personal, like integrity, health and even human life, which is logical is violent and legal course